PERANAN SEKTOR INDUSTRI PENGOLAHAN TERRHADAP PEREKONOMIAN DI KOTA BALIKPAPAN - MUTIA UTARI (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
The purpose of the research is to examine the role of the manufacturing sector toward the economy in Balikpapan city. The  research variables are sub sectors of manufacturing industry in  Balikpapan city. Her instrument analysis is Input - Output which can be seen from Table I-O of Balikpapan city 2015. The Research results show that the 10 sub-sectors of the manufacturing, which have forward orientation or high forward linkages, but have low backward linkages  value are the sector of petroleum refining industry, plastic and rubber chemical industry, food and beverage industry. While the sector which have backward orientatation or high backward linkages are textile industry, garment and leather, other industrial goods, machinery transport industry, and equipment industry. From the 10 sub-sectors of manufacturing industry, there are three most superior industries. They are food and beverage industries, plastic and rubber chemical industry, machinery transport industry and equipment industry.Keywords: Industrial Sector, Input - Output, Economy.